TATANIAGA RUMPUT LAUT DI DESA KUTUH DAN KELURAHAN BENOA, KECAMATAN KUTA SELATAN, KABUPATEN BADUNG, PROVINSI BALI - Mahayana, Ni Putu Ayuning Wulan Pradnyani; Winandi, Ratna (Forum Agribisnis, 2013)
Seaweed is one of the strategic commodities with the highest production volume in Indonesian aqua culture commodities. According to The Ministry of Marine Affairs and Fisheries, production volume of seaweed had grown at 18,18 percents in 2010.Â For the export markets, the volume and the value of this commodity was also increase at 54,87 percents. The differences between the seaweedâs price at its sea farm and the seaweedâs price at export markets indicate a high margin in the marketing system of seaweed.Â South Kuta District is one of the seaweed farming center that located in Badung Region, Bali Province. This research is used to analyze the marketing system and the efficiency of seaweed marketing system in South Kuta District. The respondents in this research are all of seaweed farmers and institutional marketing systems which involved in the distribution, such as: assemblers, agent middlemen and exporters. The marketing margin approach, the farmerâs share approach and the ratio of benefit and marketing cost approach are used to measure the efficiency of marketing system. The participation of farmer groups affects the price of seaweed and supports the quality control of standardization for export markets. The recommendation of this research is to increase the efficiency of seaweed marketing system by decreasing the water content of seaweed.